2020
DOI: 10.1016/j.anndiagpath.2020.151529
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: A mechanistic analysis placental intravascular thrombus formation in COVID-19 patients

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
0
21
0
4
Order By: Relevance
“…The most common lesions seen related to fetal vascular malperfusion (9 cases); 5 cases showed lesions of maternal vascular malperfusion [ 20 ]. It is assumed that the 5 cases reported by Mulvey et al are incorporated in the larger report by Baegen and Heller from the same institution [ 20 , 21 ]. Cribiù et al reported placentas from 9 patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common lesions seen related to fetal vascular malperfusion (9 cases); 5 cases showed lesions of maternal vascular malperfusion [ 20 ]. It is assumed that the 5 cases reported by Mulvey et al are incorporated in the larger report by Baegen and Heller from the same institution [ 20 , 21 ]. Cribiù et al reported placentas from 9 patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Thus far, evidence has not proven that pregnant women with infection are more likely to suffer from venous thromboembolism. On a recent evaluation by Mulvey et al 27 of 5 term placentas from women with SARS-CoV-2 infection who were classified as mostly without typical symptoms related to infection, all 5 indicated evidence of fetal vascular malperfusion with thrombosis. The rate of fetal vascular malperfusion in our study was relatively low and was similar in patients who presented with and without typical symptoms related to the infection.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Characteristic histopathologic findings in placentas from mothers with viral infections have been reported. 21 , 22 , 23 , 24 However, reports on placental evaluation in women with SARS-CoV-2 infection have been limited to a few case series, 25 , 26 , 27 , 28 and the association between infection and abnormal placental findings are not well known. Therefore, the objective of this study was to determine if any significant placental histopathologic changes occur after the diagnosis of SARS-CoV-2 infection in pregnancy and whether these changes are correlated with the presence or absence of symptoms typically related to the infection.…”
Section: Introductionmentioning
confidence: 99%
“…Another analysis of 5 placentas of patients with COVID-19 found focal avascular villi and thrombi in larger fetal vessels responsible for fetal circulation disorder, but the births were with healthy newborns, at term. The absence of complement deposition suggests that in these cases virus-induced procoagulant activity was systemic 49 .…”
Section: Placental Pathological Aspectsmentioning
confidence: 93%